2020
DOI: 10.21203/rs.2.19364/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and Function of the Arctic and Antarctic Marine Microbiota as Revealed by Metagenomics

Abstract: Background: The Arctic and Antarctic are the two most geographically distant bioregions on earth. Recent sampling efforts and following metagenomics have shed light on the global ocean microbial diversity and function, yet the microbiota of polar regions has not been included in such global analyses. Results: Here a metagenomic study of seawater samples (n = 60) collected from different depths at 28 locations in the Arctic and Antarctic zones was performed, together with metagenomes from the Tara Oceans. More … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The COG richness observed in this study was slightly higher but comparable to the others previously reported by studies of global oceans and coral ecosystems (Carlos et al, 2016;Varasteh et al, 2020;Zhang et al, 2020). Significant compositional differences were observed between the reef and oceanic datasets.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The COG richness observed in this study was slightly higher but comparable to the others previously reported by studies of global oceans and coral ecosystems (Carlos et al, 2016;Varasteh et al, 2020;Zhang et al, 2020). Significant compositional differences were observed between the reef and oceanic datasets.…”
Section: Resultssupporting
confidence: 88%
“…A recent study assessing antibiotic resistance genes along a pollution gradient also found highest abundance of transporters in the most polluted site (Chen et al, 2019). COGs for DNA replication, recombination and repair were also significantly overrepresented suggesting exposure to agents of DNA damage (Buckley et al, 2020;Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 82%
“…To determine the ecological distribution of the different MedAcidi-G1 genomes in the global ocean, we performed metagenomic recruitment using samples from Tara Oceans expedition (Sunagawa et al, 2015), Tara Oceans Polar Circle (Tara Oceans Consortium, C., and Tara Oceans Expedition, P, 2017), Geotraces (Biller et al, 2018), Polar biomes (Zhang et al, 2020), Tasman sea (PRJNA385736), HOT ALOHA metagenomic time and depth series (Mende et al, 2017), Malaspina expedition (Duarte, 2015), Mediterranean Sea (Haro-Moreno et al, 2017López-Pérez et al, 2017), Red Sea time and depth series (Haroon et al, 2016) and western subarctic Pacific (PRJNA398459). Metagenomic reads were trimmed using Trimmomatic v0.36 (Bolger et al, 2014) and only those readings with a Phred score of ≥30, that were ≥ 50 bp long, and without ambiguity were used for recruitment analysis.…”
Section: Metagenomic Recruitmentmentioning
confidence: 99%
“…Bacterial communities in both polar regions have been studied through 16S-rRNA analyses in the context of algal blooms (13)(14)(15), but only recently metagenomic has been applied to Arctic samples (16,17). Despite the existing research, a metagenomic time series covering a phytoplankton bloom is still lacking in the Arctic ecosystem, and so does a closer examination of polysaccharide utilisation in the whole bacterial community.…”
Section: Introductionmentioning
confidence: 99%
“…Marine bacterial communities in polar regions are dominated by Alphaproteobacteria, Gammaproteobacteria and Bacteroidetes, with an important contribution of Actinobacteria, Deltaproteobacteria and Archaea (16). The degradation of marine polysaccharides by bacterioplankton requires a high metabolic specialisation, including an appropriate repertoire of enzymes as well as an efficient system to take up the degradation products.…”
Section: Introductionmentioning
confidence: 99%